Chinese firms going global can they succeed? - Healy, Joseph C. (World Scientific, 2018)
China has increased its engagement with the world and is pursuing ambitious economic goals. Much has been written about the economic and social impact of Inbound Foreign Direct Investment (IFDI) on China with the transfer-in of Western resources and expertise. Less has been written, in an accessible way at least, on the unleashing of the entrepreneurial spirit and Outbound Foreign Direct Investment (OFDI) of China as Chinese firms have gone global.The global expansion of Chinese firms is a recent phenomenon, which is not well understood. The book is aimed at providing an important context for understanding the challenges and biases Chinese firms face while going global, using a multi-disciplinary approach weaving themes from history, contemporary Chinese politics, geopolitics, international relations, economics, finance, strategy, culture and society, together with the role of management education in developing entrepreneurs' capabilities for success.The book also explores the basis upon which Chinese firms can compete outside their domestic market by using a Four Cs' framework - core capabilities, cultural adaptability, competencies of management and country of origin. The book argues that weaknesses in several of the Four Cs' might be compensated for by the Fifth C - cooperation from government.The book will appeal to the growing legion of China-watchers and general readers who are open-minded and keen to better understand the increasing profile of Chinese firms in international markets. Are they a threat? To whom? And why?